.Net common language runtime unleashed - Burton, Kevin R. (Sams Pub., 2002)
The .NET Framework provides a runtime environment called the Common Language Runtime, which manages the execution of code and provides services that make the development of robust software easier. The Common Language Runtime (CLR) provides a solid foundation for developers to build various types of applications. Whether a developer is writing an ASP.NET application, a Windows Forms application, a Web Service, a mobile code application, a distributed application, or an application that combines several of these application models, the CLR provides huge benefits such as simplified development and the ability to integrate code written in various languages. This book is a high-end comprehensive reference to the capability of the CLR. The samples in the book have been written so that they not only illustrate a principle but give the reader a springboard to quickly translate the sample to practical, real-world applications. After reading this book, readers will be able to significantly increase their productivity by comfortably using the power and expressiveness of the Common Language Runtime in their applications. This book will take the reader beyond the syntax of C# to using and understanding the CLR to build secure, maintainable, and high performance applications.